Free electron to electride transition in dense liquid potassium - Zong, Hongxiang; Robinson, Victor Naden; Hermann, Andreas; Zhao, Long; Scandolo, Sandro; Ding, Xiangdong; Ackland, Graeme J. (Nature physics, 2021)
At high pressures, simple metals such as potassium have a rich phase diagram including an insulating electride phase in which electrons have a localized, anionic character. Measurements in the liquid phase have shown a transition between two states, but experimental challenges have prevented detailed thermodynamic measurements. Using potassium as an example, we present numerical evidence that the liquid–liquid transition is a continuous transformation from free electron to electride behaviour. We show that the transformation manifests in anomalous diffusivity, thermal expansion, speed of sound, coordination number, reflectivity and heat capacity across a wide range of pressures. The abnormalities stem from a significant change in the local electronic and ionic structure. Although primarily a pressure-induced phenomenon, there is also a thermal expansion anomaly. By establishing the electride nature of the high-pressure liquid phase, we resolve the long-standing mystery of how a liquid can be denser than a close-packed solid. Our work is relevant for high-pressure thermodynamic properties of all alkali metal liquids. Alkali metals at high pressures have a liquid–liquid transition that is difficult to study in detail. Numerical calculations now suggest that the higher-pressure state is an electride liquid, in which electrons behave like localized anions.